The Shattered Cooperation: The European Union – Russian Federation Energy Trade Under the Shadow Of Sanctions - ANDREEA - EMANUELA DRĂGOI (Global Economic Observer)
The regional conflict from Ukraine that emerged a year ago, in February 2022, has quickly evolved into a widespread economic confrontation between the West and the Russian Federation, due to the enormous amount of sanctions imposed to the latest as a retaliation for the unprovoked military invasion into the territory of an independent and sovereign state. While the Western sanctions have targeted various economic field (from finance, to energy and trade), for the purpose of this paper we have chosen to analyse the impact of the trade sanctions in the energy field while highlighting how the European Union (EU)-Russia energy trade has shrunken under the sanctions blow. This paper provides an in depth quantitative analysis of the bilateral trade between the two parties, focusing on the evolution of energy trade after the imposition of sanctions. The methodological approach uses the latest Eurostat statistics but also a qualitative analysis of the studied literature in the field to underline the huge impact of sanctions on the bilateral cooperation between EU and Russian Federation. Our main finding shows that the sanctions have seriously affected the economic cooperation between EU and Russian Federation, causing a major decrease of the bilateral trade, but the energy trade still remains important, as the enforced bans have not completely stopped the unwanted energy link between the two parties.